Scandium: Ore deposits, the pivotal role of magmatic enrichment and future exploration - Wang, Zhenchao; Li, Martin Yan Hei; Liu, Ze-Rui Ray; Zhou, Mei-Fu (Ore geology reviews, 2021)
[Display omitted] •Partial melting of fertile spinel peridotites can produce Sc-rich melts.•High water content is favorable in forming Sc-rich clinopyroxene.•Magmatic deposits are estimated to contribute about 90% of the global Sc resources. Scandium (Sc), known as the 'miracle metal', has unique properties in material sciences, and is a critical resource in the world due to the low supply but wide applications in advanced technology. Despite not extraordinarily sparse in the Earth’s crust, Sc is often dispersed and does not form ore deposits. Nonetheless, Sc can be occasionally concentrated to form magmatic, hydrothermal or supergene deposits. Magmatic deposits are estimated to contribute about 90% of the global Sc resources, in which Sc is primarily hosted in clinopyroxene ± amphibole in mafic–ultramafic intrusions. Hydrothermal enrichment of Sc is often associated with W-Sn mineralization in quartz-vein systems. Supergene deposits mainly include regolith-hosted deposits formed from weathering of mafic–ultramafic protolith and marine sediment-hosted deposits. Magmatic enrichment of Sc is essential to form many of these different types of Sc deposits. Partial melting of anhydrous fertile spinel peridotites could produce Sc-rich primary melts, whereas melts derived from garnet peridotites are generally of low Sc concentrations. Involvement of water during partial melting may not increase Sc concentrations in the primitive melts but, during fractional crystallization, the high water content can sufficiently suppress the crystallization of orthopyroxene and the Sc scavenging by orthopyroxene. Thereby, Sc could be enriched in the melts and subsequently concentrate in clinopyroxene and amphibole. Subduction environment, at where hydrous mafic–ultramafic melts could be generated, is likely favorable locality for exploring Sc deposits, such as the Sc-rich Alaskan-type mafic–ultramafic intrusions. Under favorable supergene conditions such as tropical and sub-tropical climate, regolith-hosted Sc deposits could develop from weathering of these Sc-rich mafic–ultramafic complexes.